Iodine‐DMSO‐Promoted Oxygenation of Indoles: Synthesis of Isatin and Isoindigo. Issue 3 (9th February 2022) - Rastogi, Gaurav K.; Deka, Bhaskar; Deb, Mohit L.; Baruah, Pranjal K.
Abstract: Oxygenation/oxidative self‐coupling of indole are performed to obtain isatin and isoindigo in the absence of metal catalysts. Iodine‐DMSO is used to synthesize isatin whereas Iodine‐DMSO‐K2 S2 O8 combination is used for isoindigo synthesis directly from indole in a single step. Though several methods are known for isatin synthesis from indole, most of them use large quantity of oxidants or metal catalyzed. Moreover, the primary existing process for the synthesis of isoindigo is the condensation of isatin and oxindole in the presence of an acid catalyst. But this method provides isoindigo derivatives directly from indoles. A plausible mechanism is also proposed based on the various control experiments which indicate that both the reactions proceed via radical route. It is also observed that oxygen atoms of isatin and isoindigo come from water molecule and DMSO. Abstract : Metal‐free synthesis of isatin and isoindigo through oxygenation/oxidative self‐coupling of indole are reported here. I2 ‐DMSO/ persulfate combination is used to promote the reactions. Meisoindigo, a drug used against leukemia is also synthesized.